Bodies in code : interfaces with digital media - Hansen, Mark B. N. (Mark Boris Nicola), 1965- (New York ; London : Routledge, 2006)
Bodies in Code explores how our bodies experience and adapt to digital environments. Cyberculture theorists have tended to overlook biological reality when talking about virtual reality, and Mark B.N. Hansen's book shows what they've been missing. Cyberspace is anchored in the body, he argues, and it's the body--not high-tech computer graphics--that allows a person to feel like they are really 'moving' through virtual reality. Of course these virtual experiences are also profoundly affecting our very understanding of what it means to live as embodied beings. Hansen draws upon recent work in.
Front cover; contents; the author; preface; Introduction; PART I: toward a technics of the flesh; Chapter 1. bodies in code, or how primordial tactility introjects technics into human life; PART II: locating the virtual in contemporary culture; Chapter 2. embodying virtual reality: tactility and self-movement in the work of char davies; Chapter 3. digitizing the racialized body, or the politics of common impropriety; Chapter 4. wearable space; Chapter 5. The Digital Topography of House of Leaves; Notes; References; Bibliography; Index; Back cover.
Includes bibliographical references (p. 309-318) and index
Keywords: Body schema; Digital media -- Philosophy; Human figure in art; Virtual reality -- Psychological aspects; Virtual reality in art